Evaluation of Academic Supervision Program in Improving Teachers’ Administrative Compliance in Learning at MTs Semarang - Rizca Wulandari; Laili Zakiyatul Hanafiyah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study evaluates the implementation of academic supervision in improving teachers’ compliance with instructional administration at MTs X in Semarang City. The research employed a qualitative evaluative approach using the Context, Input, Process, and Product (CIPP) model to provide a comprehensive assessment framework. Data were collected through systematic observations, in-depth interviews with the principal and teachers, and rigorous document analysis of instructional plans, teaching journals, and supervision reports. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing to ensures validity. The findings show that the supervision program has been strategically aligned with institutional needs and national education standards. However, several critical limitations were identified, particularly in documentation systems, limited access to professional development, and the lack of digital monitoring platforms. Although supervision is conducted regularly, the implementation tends to emphasize administrative inspection rather than pedagogical development, leading teachers to prepare necessary documents only shortly before the scheduled supervision. As a result, improvements in instructional documents are evident but remain situational rather than sustainable in the long term. The process lacks a consistent follow-up mechanism that addresses individual teacher challenges in the classroom. Consequently, the study recommends strengthening coaching-based supervision techniques and developing a systematic follow-up program to foster internalized professional compliance. It is essential for the principal to shift the paradigm from formal surveillance to collaborative mentorship. This transformation will ensure that administrative excellence serves as a foundation for better teaching quality, ultimately enhancing the overall educational outcomes and institutional performance within the school environment.